أثر العلاقات العامة الإلكترونية في اتخاذ القرار الشرائي من حيث اختيار العلامة التجارية ومرحلة ما بعد الشراء (دراسة تطبيقية على شركات الاتصالات الخليوية في سورية ) - علي ندى; مربية أحمد (Latakia University Journal - Economic and Legal Sciences Series, 2018)
يتناول البحث أثر العلاقات العامة الالكترونية في اتخاذ القرار الشرائي للمستهلك في شركات الاتصالات الخليوية العاملة في سورية (سيريتل و MTN). وذلك من خلال دراسة الأثر بين العلاقات العامة الالكترونية واتخاذ القرارات الشرائي من حيث (اختيار العلامة التجارية، مرحلة ما بعد الشراء). اعتمد البحث على المنهج الوصفي، وشمل مجتمع البحث عينة زبائن شركات الاتصالات الخليوية المتواجدين في مدينة دمشق حيث تم توزيع (400) استمارة أعيد منها (374) استبانة بنسبة استجابة بلغت (93%)، وباستخدام الأساليب الإحصائية المناسبة تم التوصل إلى النتائج الآتية: 1- أظهرت النتائج وجود علاقة طردية ذات دلالة معنوية بين العلاقات العامة الالكترونية المستخدمة واتخاذ القرار الشرائي من حيث اختيار العلامة التجارية. 2- أظهرت النتائج وجود علاقة طردية ذات دلالة معنوية بين العلاقات العامة الالكترونية المستخدمة واتخاذ القرار الشرائي من حيث مرحلة ما بعد الشراء. 3- بينت نتائج الدراسة أنه لا يوجد فروق معنوية ذات دلالة فيما يتعلق بأثر العلاقات العامة الالكترونية على اتخاذ القرار الشرائي تبعاً للنوع "الجنس". 4- بينت نتائج الدراسة أنه يوجد فروق معنوية ذات دلالة فيما يتعلق بأثر العلاقات العامة الالكترونية على اتخاذ القرار الشرائي تبعاً "للمرحلة العمرية"، حيث أن الفئة العمرية الشابة (25-35) أكثر تأثراً بالعلاقات العامة الالكترونية في مرحلة ما بعد الشراء. This study aims to define the Online Public Relation tools, its importance, specifications and to which extent the companies whose work in telecommunications’ sector in Syria are using these tools. What the impact of these tools (Website, Social Network) on the Customer’s Purchasing Decision through 2 stages; the stage of select the brand and actual decision to buy, and the post-purchase behavior. The research adopted the descriptive approach. The research community is the customers of cellular communications companies which are working in Syria: Syriatel and MTN. Survey strategy is used in this research, particularly the questionnaire technique which lead to receive 374 valid responses out of 400 distributed questionnaires. by using appropriate statistical methods, the finding show that: 1- There is a significant positive correlation between the efficiency of the Online Public Relation and Customer’s Purchasing Decision though the stage of select the brand. 2- There is a significant positive correlation between the efficiency of the Online Public Relation and Customer’s Purchasing Decision though post-purchase stage. 3- There is no significant difference with regard to the Impact of the Online Public Relation on Customer Purchasing Decision relating to the gender. 4- There is a significant difference with regard to the Impact of the Online Public Relation on Customer Purchasing Decision relating to the “Age”, particularly those who are younger tend to be influenced much more than other age’s group by the online public relation in post-purchase stage.